ENABLING THE MANAGEMENT EVOLUTION IN INFORMATION TECHNOLOGY DOMAIN: ANALYZING THE INCREMENTAL AND TANGIBLE MANAGEMENT BY OUTCOME (IT MBO) - et. al., Ravi Kumar Jain (International Journal of Modern Agriculture, 2021)
Management is an evolving practice based on the evolution of knowledge that is required to be applied to solve real-life problems. These real-life work problems and the implementation of knowledge to resolve them is done in the form of projects. With the omnipresence of digitalization, the 21st century, and hereon, we are heavily dependent on how we manage our Information Technology projects. And thus, the management of Information Technology projects becomes one of the most critical aspects of applying knowledge and to sustain further evolution. In this respect, we have to consider, what are some of the limitations as well as what are the indicators of the natural evolution of management in the Information Technology domain. There are different structures in which Information Technology projects are categorized, and there are many management principles, practices, and methodologies aligned with each of them. But we have to find a common strand that would act as a unifying factor that is bound to the basics and provides for the minimum required to sustain this evolution. This study is aimed at finding this factor (or factors) that unifies, simplifies, and standardizes any Information Technology project. Incremental and Tangible Management by Outcome (IT MBO) is the logical evolution of management in the Information Technology domain, which is analyzed through a structured literature review and extensive background industry work building on the two most important constructs of ‘incremental approach’ and ‘tangible output’. This paper would explain the analysis of suitable literature review for Incremental and Tangible Management by Outcome (IT MBO), its application for an Information Technology project, and its relationship with these constructs.